2012
DOI: 10.1002/kin.20601
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature dissociation of ethyl radicals and ethyl iodide

Abstract: The decomposition of ethyl iodide and subsequent dissociation of ethyl radicals have been investigated behind incident shock waves in a diaphragmless shock tube by laserschlieren (LS) densitometry (1150-1870 K, 55 ± 2 Torr and 123 ± 3 Torr). The LS density-gradient profiles were simulated assuming that the initial dissociation of C 2 H 5 I proceeded by 87% C I fission and 13% HI elimination. Excellent agreement was found between the simulations and experimental profiles. Rate coefficients for the C I scission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
5
27
0
Order By: Relevance
“…Recently, Yang and Tranter performed a high‐temperature study of ethyl iodide and ethyl radical decomposition behind incident shock conditions of 55 and 123 Torr and in the temperature range of 1150 − 1870 K. The results of their study were in very good agreement with the calculations of Miller and Klippenstein at 123 Torr and between 10% and 20% lower at the lower pressure.…”
Section: Mechanism Developmentsupporting
confidence: 56%
“…Recently, Yang and Tranter performed a high‐temperature study of ethyl iodide and ethyl radical decomposition behind incident shock conditions of 55 and 123 Torr and in the temperature range of 1150 − 1870 K. The results of their study were in very good agreement with the calculations of Miller and Klippenstein at 123 Torr and between 10% and 20% lower at the lower pressure.…”
Section: Mechanism Developmentsupporting
confidence: 56%
“…Figure shows the C 2 H 5 I decomposition branching ratio, k R1 /( k R1 + k R3 ), from our optimized rate parameters. This branching ratio is 0.936 at 900 K, decreasing nearly linearly to 0.834 at 1400 K. The extrapolated branching ratio is 0.738 at 2000 K. Kumaran et al suggested a branching ratio of 0.87 ± 0.11 for the temperature range 950−2050 K. Yang and Tranter accepted this ratio but noted that their experimental data could also be reproduced with any branching ratio higher than 0.87 (cf. the caption of Fig.…”
Section: Mechanism Optimizationmentioning
confidence: 97%
“…The dashed lines show the 3 σ uncertainty limits. The shaded areas show the uncertainty ranges of the reported branching ratios in the corresponding temperature region: (1) 0.92 ± 0.06, Miyoshi et al ( p = 0.6–1.9 bar); (2) higher than 0.87, Yang and Tranter ( p = 0.07–0.16 bar); (3) 0.87 ± 0.11, Kumaran et al ( p = 0.1–0.7 bar); and (4) 0.7 ± 0.1, Weber et al ( p = 1.5 bar).…”
Section: Mechanism Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of methyl iodide we expect the pyrolysis reaction mechanisms to include C−I bond fission reactions, which may proceed as: CH3ICH3·+ I·C+I·+ H2as well as through molecular elimination of HI: CH3IC + HI +normalH2…”
Section: Challenges Of On‐line 2h/1h Measurements In Cnhnxn Compoundsmentioning
confidence: 99%